2019
DOI: 10.1039/c8bm01483c
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine functionalized poly(glycidyl methacrylate) nano-assemblies for photodynamic inactivation of bacteria

Abstract: Self-assembled PGED-Pc nanoparticles are able to inactivate bacteria via the generation of reactive oxygen species in aqueous solution, while a facile immobilization strategy sheds light on the engineering of self-sterilizing surfaces to combat bacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…In another study, Xu and co‐workers synthesized zinc(II)monoamino Pc, which was conjugated to poly(glycidyl methacrylate) via a ring‐opening reaction (Figure 10 c). [81] When dispersed in aqueous solution, self‐assembled nanoparticles (PGED‐Pc NPs) were formed. Photophysical measurements showed that PGED‐Pc NPs generated mainly superoxide/H 2 O 2 instead of the expected 1 O 2 .…”
Section: Molecular Photosensitizersmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Xu and co‐workers synthesized zinc(II)monoamino Pc, which was conjugated to poly(glycidyl methacrylate) via a ring‐opening reaction (Figure 10 c). [81] When dispersed in aqueous solution, self‐assembled nanoparticles (PGED‐Pc NPs) were formed. Photophysical measurements showed that PGED‐Pc NPs generated mainly superoxide/H 2 O 2 instead of the expected 1 O 2 .…”
Section: Molecular Photosensitizersmentioning
confidence: 99%
“…In another study,X ua nd co-workers synthesized zinc(II)monoaminoP c, which was conjugatedt op oly(glycidyl methacrylate) via ar ing-opening reaction (Figure 10 c). [81] When dispersed in aqueous solution,s elf-assembled nanoparticles (PGED-Pc NPs) weref ormed. Photophysicalm easurements showedt hat PGED-Pc NPs generated mainly superoxide/H 2 O 2 insteado ft he expected 1 O 2 .N evertheless,o btained NPsw ere able to inactivateb oth Gram-negative and Gram-positive bacteria in aqueous solutions,w ith am inimum bactericidal con- centrationo f1 28 mgmL À1 for E. coli and 4 mgmL À1 for S. aureus.…”
Section: Supramolecular and Polymer-based Carrier Systemsmentioning
confidence: 99%
“…Relevant to this work, photodynamic therapy (PDT) is a promising prospect in delivering these desired outcomes. [ 11 ] The in situ generation of reactive oxygen species (ROS), such as cytotoxic singlet oxygen ( 1 O 2 ), is an attractive strategy considering the abundance of environmental oxygen. [ 12 ] In this vein, the incorporation of anthraquinone, [ 13 ] benzophenone, [ 14 ] xanthene, [ 15 ] and porphyrin [ 16 ] photosensitizers into a variety of substrates to convey biocidal activity has been widely explored.…”
Section: Introductionmentioning
confidence: 99%
“…This need can be achieved by incorporating antibacterial materials into face mask filters. Conventional strategies of using antibacterial agents such as Ag ions, 29 Cu ions, 30 metal oxides, 31 , and photosentisizers 32 are not very suitable because most of these materials are toxic to humans and environmentally unfriendly.…”
Section: Introductionmentioning
confidence: 99%